Disentangling knowledge production and data production. Issue 7 (16th July 2020) - Baker, Karen S.; Mayernik, Matthew S.
Abstract: With today's increasing attention to open science and open data, knowledge production and data production have significant impacts on both research and policy arenas. We scrutinize the concept of data production in relation to knowledge production in the earth and environmental sciences. We present three empirical cases that illustrate issues arising when knowledge production and data production as interdependent but distinct processes are not clear in the mind of researchers and policymakers. A two‐stream model is developed that highlights their interplay yet avoids the conflation of knowledge and data production. This approach highlights knowledge and data in terms of processes rather than stable objects or assets. Further, we suggest that considering knowledge and data production in relation to their development by communities rather than as commodities helps in understanding the debates and issues that arise in contemporary research practice.